ANALISIS KEKUATAN DAN KELEMAHAN KOPERASI MENGHADAPI HEGEMONI PASAR MODERN - Ramadhan; Badrus Soleh; Achmad Junaidi (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2026)
Cooperatives in indonesia constitute the foundational pillar of the national economy and hold a constitutionally strategic position. However, their existence is currently under pressure from the hegemony of modern markets, which are dominated by large capital interests and the penetration of digital technology. This study aims to provide a comprehensive mapping of the internal strengths and fundamental weaknesses of cooperatives within the Indonesian market system through a systematic literature review. The analysis examines 24 selected scholarly journal articles published between 2019 and 2026 to ensure the data remains relevant to current economic dynamics. The synthesis indicates that the primary strengths of cooperatives lie in their social capital, the principle of kinship (asas kekeluargaan) which fosters member loyalty, and their potential for digital adaptation as a tool to mitigate economic recessions and the dominance of multinational corporations. Conversely, the findings confirm chronic, unresolved weaknesses, including low managerial professionalism, limited access to capital, and small economies of scale that hinder price efficiency in competitive markets. External challenges, such as the Fourth Industrial Revolution and shifting consumer behaviors, demand that cooperatives undergo immediate structural transformation. This article concludes that the key to cooperative sustainability in the face of modern market hegemony lies in the implementation of agile strategic management, service digitalization, and the strengthening of strategic partnerships. Policy recommendations are directed toward reinforcing regulations that protect the cooperative ecosystem without compromising its inherent competitiveness within the market mechanism.